Constructing mainstay-body structure in heterocyclic aramid fiber to simultaneously improve tensile strength and toughness - Yang, Cheng; Wu, Hang; Dai, Yu; Zhang, Dajie; Xu, Ruopei; Luo, Longbo; Liu, Xiangyang (Composites. Part B, Engineering, 2020)
High-performance polymer fibers have broad applications in composites due to high strength and excellent toughness. However, the enhancement in tensile strength often results in a decrease in elongation at break, and simultaneous increase of strength and toughness is still challenging for aramid fiber. Herein, an effective method based on relaxation time theory is proposed to simultaneously enhance the tensile strength and elongation at break for heterocyclic aramid fiber. Ultra-high molecular weight heterocyclic aramid (HMPBIA) was added in the heterocyclic aramid (PBIA) spinning dope to prepare fibers. The structure evolution of fiber is studied in detail combining with experiment and simulation. Results of Molecular Dynamics simulations prove that HMPBIA acts as a role of mainstay by maintaining straight chain conformation in highly oriented fibers. This unique mainstay-body structure weaken slippage between molecular chains when the fiber is subject to tension. Further characterizations by small angle X-ray scattering (SAXS) and scanning electron microscope (SEM) confirm the formation of mainstay-body structure in the fiber, which improves tensile strength and elongation at break by 17.7% and 16.7%, respectively. [Display omitted] •HMPBIA is added into the spinning solution, and it doesn't lead to too high viscosity while ensuring compatibility.•The orientation evolution of fibers was studied from the point of relaxation time of macromolecular chains.•HMPBIA plays a role like a mainstay in PBIA fiber, which helps to increase the average length of fibrils.•Enhanced tensile strength and elongation at break of PBIA fiber are simultaneously realized.